Organizational Communication and Employee Performance in Service Companies in West Papua - Nelson Mansoara; Roberth Kurniawan Ruslak Hammar (Journal Development Manecos, 2026)
Organizational communication has increasingly been recognized as a strategic organizational capability that supports employee effectiveness and organizational performance, particularly within service-oriented industries. However, empirical evidence examining this relationship in geographically dispersed and culturally diverse regions remains limited. This study investigates the effect of organizational communication on employee performance in service companies located in Manokwari, West Papua, Indonesia. A quantitative research design was employed, and data were collected through structured questionnaires administered to 100 employees working in banking, telecommunications, hospitality, transportation, retail, and public service organizations. Respondents were selected using purposive sampling based on predefined eligibility criteria. The measurement instruments were adapted from established organizational communication and human resource management literature and analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results demonstrate that organizational communication exerts a positive and significant effect on employee performance (β = 0.756, t = 13.842, p < 0.001). The model explains 57.1% of the variance in employee performance (R² = 0.571), indicating that communication represents a substantial organizational determinant of performance outcomes. The findings suggest that communication characterized by clarity, openness, information accuracy, effective coordination, and constructive feedback enhances employees’ ability to perform their duties efficiently and collaboratively. Beyond confirming existing organizational communication theory, this study contributes to management literature by demonstrating the strategic importance of communication within service organizations operating in a geographically dispersed, culturally diverse, and infrastructure-constrained environment. The findings further imply that managers should prioritize the development of transparent, participative, and responsive communication systems to strengthen employee performance and organizational effectiveness.